Modification Of Rheological Properties Of Asphalt Effect Of Addition Of Asphaltenes And Oxidized Asphaltenes On The Compatibility Of Asphalt- Sulfur Blends (Baghdad Science Journal, 2025)
This study is a complementary one to an extended series of research work that aims to produce a thermodynamiclly stable asphalt –sulfur blend. Asphalt was physically modified wiht different percentages of asphaltenes , oxidized asphaltenes and then mixed with sulfur as an attempt to obtaine a stable compatible asphalt-sulfur blend.The homogeneneity of asphalt-asphaltenes[oxidized asphaltenes]-sulfur blends were studied microscopically and the results are prsented as photomicrographs.Generally more stable and compatible asphalt-sulfur blends were obtained by this treatment.